Late‐onset visceral varicella‐zoster virus infection presented as acute liver failure after allogeneic hematopoietic stem cell transplantation. Issue 4 (14th June 2019) - Kikuchi, Taku; Arai, Mari; Koda, Yuya; Kato, Jun; Shimizu, Takayuki; Katano, Harutaka; Fujii‐Nishimura, Yoko; Sakamoto, Michiie; Ebinuma, Hirotoshi; Nakamoto, Nobuhiro; Kanai, Takanori; Okamoto, Shinichiro; et al.
Abstract: Although much less common than localized zoster, initial presentation of varicella‐zoster virus (VZV) as visceral infection can occur especially after allogeneic hematopoietic stem cell transplantation (HSCT). We herein report a case of post‐transplant visceral VZV infection presenting as fatal acute liver failure. It developed 4 years after allogeneic HSCT when a long‐term prophylactic anti‐VZV agent administration was discontinued. VZV should be listed as a causative pathogen of acute liver failure even years after allogeneic HSCT. Indication for, and duration of anti‐VZV prophylaxis should be further investigated.